S'approprier les sens pour dépasser la clôture: les religieuses anglaises s'inscrivent dans la mission - Laurence Lux-Sterritt (Etudes Epistémè)
In the reformed England of the seventeenth century, asserting one’s Catholic faith was a militant gesture. Other than the “Church papists”, who occasionally conformed, and the “recusants” who refused to accommodate the established Church, many Catholics chose exile on the Continent. Between 1598 and 1678, twenty English convents were founded to allow women to commit to their faith, body and soul. Yet despite the ardour of their zeal, they were not allowed to take part in the Counter-Reformation efforts in the same way as men. In the Benedictine order, for instance, monks were able to work in the mission, a possibility which the nuns were absolutely denied. In a gendered role distribution, the post-Tridentine Church insisted that nuns must be cloistered; therefore, contrary to their male counterparts, English Benedictine nuns could not become missionaries. Yet, some communities developed strategies to create a space for themselves in that mission, even without leaving the enclosure. Whereas monastic tradition incited nuns to despise their bodies and to yearn for an entirely spiritual form of perception, the Ghent community wrote texts of experience which staged both the senses of mysticism and those of nature. When physical senses served spiritual perception, they became, for that community, a means to transcend the walls of enclosure and to write themselves into the otherwise male mission of Catholic revival.